The origins of the legal and political system of Kazakhstan: History and modernit (Journal of actual problems of jurisprudence, 2018)
To understand the political and legal system of Kazakhstan, the knowledge of the historical foundations and dynamics of those processes that occur in the country is of great importance. In order to achieve this goal, it is important to use historical and comparative methods of research. Only on their basis can you make certain forecasts about the future of the country, its political and legal system. The authors considers the origins of the political and legal system of Kazakhstan from the point of view of history and modernity, paying special attention to the definitions used. So, within the framework of studying the origins of the political system of Kazakhstan, special attention is paid to the concept of the political system of society, the theories existing in this sphere, as well as the typology of political systems. The authors emphasizes the special role of the state, which is the central element of the political system of society. The article considers the history of the political system of Kazakhstan since the creation of the Kazakh Khanate, which arose on the wreckage of the Golden Ord, ending with the Soviet period and the features of the political system of modern Kazakhstan. The specificity of the modern political system of Kazakhstan lies in the leading role of the state, which has a decisive influence on the country’s political system. When considering the legal system of Kazakhstan, the main emphasis was placed on the delineation of the concepts of «legal system», «system of law» and «system of legislation». At the same time, the authors proceeds from how these terms are understood in Kazakhstan and other post-Soviet states. An appeal to the history of the formation of the legal system of Kazakhstan begins with the era of the Kazakh Khanate (15th century), after which the authors dwells on the peculiarities of the rights of the Kazakhs within the Russian Empire and the Soviet Union. At the end of this section, the features of the legal system of modern Kazakhstan are analyzed. The authors formulates the conclusion that the legal system built in Kazakhstan and in Russia is of the same type, which meets the foreign policy course of Kazakhstan, aimed at tight integration of post-Soviet state strikes. Key words: Kazakhstan, political system, legal system, sources, functions of the state.